2002
DOI: 10.2108/zsj.19.1141
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genetic Diversity in Insular Populations of Nasutitermes takasagoensis (Isoptera: Termitidae) Analyzed by AFLP Markers

Abstract: Dispersal ability and degree of inbreeding in a population can indirectly be assessed using genetic markers. In general, it was suggested that winged termites are not able to fly distances greater than several hundred meters. Here, amplified fragment length polymorphism (AFLP) was used to analyze genetic diversity, population substructure, and gene flow among insular populations of the termite Nasutitermes takasagoensis (Isoptera: Termitidae) in the Yaeyama Islands, Okinawa, Japan. Samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Direct fi eld observations on swarming alates indicated that the mean fl ight distance is in the order of several hundreds of meters (Nutting, 1969; see also Brandl et al, 1996;García et al, 2002). Due to the constrained active dispersal of termites one might expect considerable and variable genetic differentiation between nearby populations.…”
Section: Introductionmentioning
confidence: 99%
“…Direct fi eld observations on swarming alates indicated that the mean fl ight distance is in the order of several hundreds of meters (Nutting, 1969; see also Brandl et al, 1996;García et al, 2002). Due to the constrained active dispersal of termites one might expect considerable and variable genetic differentiation between nearby populations.…”
Section: Introductionmentioning
confidence: 99%
“…The very short-distance attraction in termites may be explained The number of termites used for each test is indicated at the base of the columns by the relatively short distance they can fly (5-100 m on average) (Nutting, 1969;Jones et al, 1988), although some spectacular distances traversed in some species have been inferred or recorded (Harvey, 1934;Jones et al, 1988;García et al, 2002;Messenger and Mullins, 2005). Termite sex-pairing pheromones are considered to possess a dual role with the long-distance attraction of females and males, and the short-distance attraction maintaining tandem behavior (Nutting, 1969;Bordereau and Pasteels, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Field sampling N. takasagoensis is distributed in the Ryukyu Islands (Garcı´a et al, 2002(Garcı´a et al, , 2004, Taiwan and Yunnan Province of China (Morimoto, 2000). Four colonies of N. takasagoensis were collected in April 2002 and 2003 from Iriomote Island, and in June 2002 and May 2004 from Ishigaki Island, Okinawa, Japan.…”
Section: Methodsmentioning
confidence: 99%